2012
DOI: 10.1021/jp212247a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crown Ethers on the Ground and Excited State Reactivity of Samarium Diiodide in Acetonitrile

Abstract: Electron transfer from the ground and excited states of Sm[15-crown-5](2)I(2) complex to a series of electron acceptors (benzaldehyde, acetophenone, benzophenone, nitrobenzene, benzyl bromide, benzyl chloride, 1-iodohexane, and 1,4-dinitrobenzene) was investigated in acetonitrile. Electron transfer from the ground state of the Sm(II)-crown system to aldehydes and ketones has a significant inner sphere component indicating that the oxophilic nature of Sm(II) prevails in the system even in the presence of bulky … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…In most of the papers reporting the reaction of SmI 2 with benzyl halides, the benzylic system was used as a model or a vehicle to explore the landscape of SmI 2 capabilities. A number of examples of these are the lifetime of excited SmI 2 ,6 the issue of inner sphere versus outer sphere electron transfer,7 as a mechanistic probe for the reactions of SmI 2 –water,8 the effect of crown ethers on SmI 2 reactions,9 the effect of water,10 glyme,11 hexamethylphosphoramide (HMPA)12 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the papers reporting the reaction of SmI 2 with benzyl halides, the benzylic system was used as a model or a vehicle to explore the landscape of SmI 2 capabilities. A number of examples of these are the lifetime of excited SmI 2 ,6 the issue of inner sphere versus outer sphere electron transfer,7 as a mechanistic probe for the reactions of SmI 2 –water,8 the effect of crown ethers on SmI 2 reactions,9 the effect of water,10 glyme,11 hexamethylphosphoramide (HMPA)12 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, more recent studies indicated that crown ethers have preferences for +2 state over +3 and, as a result, these ligands act as a stabilizer to divalent state. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the numerous works concerning self-assembled monolayers of macrocyclic complexes with inorganic and organic molecules and ions have been published recently by various research groups worldwide [38][39][40][41]. The numerous crown-containing compounds with various substituents are promissing for application in molecular devices [42], chromatography [43], catalysis [44,45], biomedical fields [46,47], photovoltaics [48,49], hybrids [50,51] and special [52][53][54] materials. …”
Section: Discussionmentioning
confidence: 99%